Pelatihan Inovasi Service Excellent Kepada UMKM Komunitas Jakarta Entrepreneur - Christin Setiawan; Dian Octarina; Anis Darsiah (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
This Community Service (PKM) activity aims to increase the understanding of MSME players in Jakarta about the importance of superior service to increase customer satisfaction and loyalty. In facing intense competition, it is hoped that understanding the principles of excellent service can help MSMEs implement effective service strategies, attract new customers and support local economic growth. The method for implementing outreach activities regarding service excellence innovation is designed to ensure a comprehensive and integrated approach through a series of activities that include direct assistance, counseling, outreach and consultation. Outreach activities regarding service excellence innovation in Gambir District have had a significant impact on the understanding and practice of excellent service among Micro, Small and Medium Enterprises (MSMEs), especially those who are members of the Jakarta Entrepreneur community. Participants demonstrated increased understanding of the key elements of good customer service, including effective communication, listening skills, and responsiveness to customer needs.